2016
DOI: 10.1021/acsami.6b09175
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer Modulated Self-Assembly in Poly(aryl ether) Dendron Derivatives with Improved Stability and Transport Characteristics

Abstract: Alteration of native gelation properties of anthracene and pyrene cored first generation poly(aryl ether) dendrons, G1-An and G1-Py, by introducing a common acceptor, 2,4,7-trinitro-9H-fluoren-9-one (TNF), results in forming charge transfer gels in long chain alcoholic solvents. This strategy leads to significant perturbation of optical and electronic properties within the gel matrix. Consequently, a noticeable increase of their electrical conductivities is observed, making these poly(aryl ether) dendron based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Additional support behind this interaction came from the long‐range diffraction peak, in powder XRD analysis of PYNAP (Figure S13). The notable reflection peak, appeared at 2θ=25.01°, indexed a d‐spacing of 3.57 Å and confirmed the presence of this intermolecular π⋅⋅⋅π interaction . On the other hand, obvious flipping of naphthalene unit around the single bond, connected with keto group, caused a certain amount of twisting in the structure.…”
Section: Resultsmentioning
confidence: 61%
“…Additional support behind this interaction came from the long‐range diffraction peak, in powder XRD analysis of PYNAP (Figure S13). The notable reflection peak, appeared at 2θ=25.01°, indexed a d‐spacing of 3.57 Å and confirmed the presence of this intermolecular π⋅⋅⋅π interaction . On the other hand, obvious flipping of naphthalene unit around the single bond, connected with keto group, caused a certain amount of twisting in the structure.…”
Section: Resultsmentioning
confidence: 61%
“…The peripheral o ‐benzoxy rings of PAE dendrons now become strongly electronegative in character, with respect to the central N atom of the TPA core. The stability of such highly polarized states of TPAPAE ⋅+ can ameliorate the conduction pathways in a single‐component molecular assembly, without the need of any dopants/additives . However, prohibiting deactivation of such states is difficult, which demands for a higher order assembly.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of such highly polarized states of TPAPAE · + can ameliorate the conduction pathways in as ingle-component molecular assembly,w ithout the need of any dopants/additives. [44] However,p rohibiting deactivation of such states is difficult, whichd emands for ah igher order assembly.T he self-assembled nanocrystalse xhibit tremendous electrochemical stabilization of TPAPAE mixed valence states, upon applying electrical voltage. Cyclic voltammograms (CV) for the xerogel-coated electrodes show ah igh stabilization of mixed valence states,w ith an onset of two irreversible oxidation potentials at E ox 1 = 0.34 V and E ox 2 = 0.46 V, (Figure S13 a) corresponding to TPAPAE · + and TPAPAE ·2 + ,r espectively.T he irreversiblee lectrochemical stability of the charge carriers is retained even after 20 cycles.T his is in contrastt ot he reversible redox response of solidT PAPAE, which showss table and reversible redox responsea tasimilar potentialw ith lower current (Figure S13 b).…”
Section: Stabilization Of Mixed-valence States and Amplified Optoelecmentioning
confidence: 99%
See 1 more Smart Citation
“…Arago et al, [47,48] have performed the benchmark studies using wB97X-D functional against several dispersion-corrected hybrids and highly correlated methods. They found that the wB97X-D exhibits the best performance to deal with charge-transfer excitations in a balanced way.…”
Section: Computational Detailsmentioning
confidence: 99%